Alternatives to Arrest for Illicit Opioid Use: A Joint Criminal Justice and Healthcare Treatment Collaboration - Andrea J Yatsco; Rachel D Garza; Tiffany Champagne-Langabeer; James R Langabeer (SAGE Publishing, 2020)
Opioid overdoses continue to be a leading cause of death in the US. This public health crisis warrants innovative responses to help prevent fatal overdose. There is continued advocacy for collaborations between public health partners to create joint responses. The high correlation between persons with opioid use disorder who have a history of involvement in the criminal justice system is widely recognized, and allows for treatment intervention opportunities. Law enforcement-led treatment initiatives are still relatively new, with a few sparse early programs emerging almost a decade ago and only gaining popularity in the past few years. A lack of published methodologies creates a gap in the knowledge of applied programs that are effective and can be duplicated. This article seeks to outline an interagency relationship between police and healthcare that illustrates arrest is not the only option that law enforcement may utilize when encountering persons who use illicit substances. Program methods of a joint initiative between law enforcement and healthcare in a large, metropolitan area will be reviewed, supplemented with law enforcement overdose data and statistics on law enforcement treatment referrals.